PENGARUH KONSENTRASI KEPEMILIKAN INSTITUSIONAL , UKURAN PERUSAHAAN DAN KOM POSISI DEWAN KOMISARIS TERHADAP MANAJEMEN LABA - Sufitrayati Sufitrayati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2015)
Concentration on institutional ownership is share ownership by institutions (institutions or companies) which can control management through an effective monitoring process so that it can influence management in taking earnings management actions. According to Stapledon (1999: This research is an empirical study, namely the study of real facts or data that is systematically collected and tested. This analysis aims to find a relationship between the dependent variable and one or more independent variables. Partially, the concentration of institutional ownership has an effect. negative to earnings management This can be interpreted that the greater the concentration of institutional ownership, the smaller the company's earnings management. The variable company size as measured by total assets has a negative effect on earnings management. Generally, companies that have relatively large total assets can operate with a higher level of efficiency compared to companies with lower total assets The composition of the board of commissioners has a negative effect on earnings management. This means that the greater the composition of the board of commissioners, the smaller the earnings management involved do company. Conversely, the smaller the composition of the board of commissioners, the greater the company's earnings management.